Identifying Media Effects Through Low-Cost, Multiwave Field Experiments. (3rd April 2019) - Gross, Kimberly; Porter, Ethan; Wood, Thomas J.
Abstract : Field experiments are notoriously difficult to implement when studying media effects. They are often prohibitively expensive, require the cooperation of a nonacademic entity, and measure effects some time after exposure to treatment. In this article, we outline a design for low-cost, multiwave field experiments of media effects. Researchers can implement this design on their own and can control the timing of when they measure effects. We demonstrate the feasibility of the design with an application to the study of presidential debates.